MANAJEMEN HIPERTENSI DENGAN TREATMENT NON-FARMAKOLOGI : Hypertension Management with Non-Pharmacological Treatment - Wiliarisa Prita Purwanti; Ayu Puspita Damayanti; Maya Miftahul Jannah (Forind Press, 2024)
Management of hypertension therapy must be carried out throughout life, both pharmacological and non-pharmacological therapy, to reduce the risk of complications and improve the quality of life of the elderly. This causes the need for assistance through providing education for elderly people who suffer from hypertension in order to achieve controlled blood pressure and reduce the symptoms of hypertension so that the risk of complications can be reduced. The design of this research is a systematic review. The search for articles discussed in this study used several databases, including Pubmed, Proquest, and ScienceDirect, with a time span of 2012 to 2022. The keywords used to search for these articles were hypertension management, hypertension treatment, non-pharmacological treatment. The type of article used is a research article. The articles collected were then re-selected using inclusion criteria, namely: 1) the aim of the article was to analyze the effectiveness of non-pharmacological treatment in hypertension management, 2) it was experimental research, as well as exclusion criteria, namely 1) it was not a full text article, 2) the article did not use English. Based on 23 selected articles, non-pharmacological interventions help reduce the daily dose of antihypertensive drugs and delay the progression from prehypertension to the hypertensive stage.